The Impact of Covid 19 on Consumption Spending in Egypt - Hashem, Eman (The Arab Journal of Administration, 2023)
Covid 19 is one of the worst economic crises faced the Egyptian and global economy .The study aims to investigate the impact of covid 19 crisis on consumption spending and the nature of consumption patterns in Egypt. The study analyzed consumption spending and patterns of consumption spending in Egypt. The study also estimated the spending elasticity of different commodities groups in Egypt to identify the structural changes of spending patterns. Also, the study compared between the impact of the global financial crisis and the covid 19 crisis on the labor market, income, prices and consumption spending. In addition, a questionnaire comprising 384 persons from different governorates was conducted to find out the impact of the covid 19 crisis on the pattern of consumption spending in Egypt. The study found that the covid 19 crisis affected consumption spending in Egypt as a result of the impact of the covid 19 crisis on both income and prices. Also, The covid 19 crisis affected the pattern of consumption spending. The demand increased for food and beverages, services and health care, communications sectors, while the demand decreased for restaurants and hotels, clothes and footwear, transportation, culture and recreation. By comparing the impact of the global financial crisis and the covid 19 crisis, we found that the impact of the covid 19 crisis on consumption spending in Egypt is greater than the impact of the global financial crisis. The sectors most affected by the global financial crisis were the tourism sector, the Suez Canal and the manufacturing sector, while the sectors most affected by the covid 19 crisis were tourism, transportation, restaurants and hotels, culture and recreation, the informal sector and the export sector. The study also found that with regard to food and beverages, consumption increased during the covid 19 crisis for items: vegetables/ dairy, cheese and eggs/ grains and bread, while consumption decreased for items: sugar and sugar foods, and non-alcoholic beverages.